(untitled) (Research, Society and Development, 2023)
The aim of this work was to conduct a socioeconomic and demographic survey of cannabis users, addressing the form of use, the user’s perception of their health, and their position regarding the legalization of the plant for medicinal purposes. The study is of the observational cross-sectional type, from which quantitative analyses were performed to outline an overview of the study objective. The research consists of a survey involving the main purposes of marijuana use. This survey was conducted through a form using Google Forms®. This study observed a population of 237 people, predominantly young, with the majority of respondents being from white and brown ethnicities, of a high economic class, with superior education and a positive self-perception of health. Our study showed that a significant proportion of respondents had already tried marijuana at some point in their lives, around 83.8%, and 61% reported improvements in comorbidities with the use of cannabis. The most frequent form of use was smoked for recreational purposes. The majority of participants knew people who used marijuana for medicinal purposes, around 72.5%. Furthermore, 91% of participants who affirmed that cannabis has benefits in the medical field had completed or incomplete higher education. It became clear that it is necessary to plan policies that facilitate access to cannabis-based medications without excessively burdening the product, in addition to clarifying to the population the potential benefits of cannabis as a therapeutic option for numerous comorbidities.